Contesting security : strategies and logics - Balzacq, Thierry (New York : Routledge, 2015)
'This book investigates to what extent the'logic of security', which underpins securitization, can be contained, rolled back or dismantled. Attempts to study how and whether desecuritization can be contested is faced with two main obstacles: (1) conflict between proponents of desecuritization and students of emancipation; (2) disagreement between scholars of each camp upon the meaning of the concept they use and upon what it entails in practice. Recent attempts to overcome these obstacles have led to the evolution of two new concepts: resistance and resilience. However, individually, the contribution of these concepts is restricted by their singular interpretation of the subject. One aim of this volume is to bring different approaches that aim to counter security logic to confront one another and substantiate their respective analytical value, through empirical evidence. The book comprises four sections, each investigating one specific modality of contesting security: desecuritization, emancipation, resistance and resilience. The overriding objective of this volume is to clearly map out the different ways in which a dominant register of meaning that shapes a specific security formation is debased. These strategies are examined, compared and assessed, in different political and cultural environments. This book will be of much interest to students of critical security studies, securitisation theory, social theory, and IR in general'--
Legitimacy and the'Logic' of Security / Thierry Balzacq -- Security and Surveillance Contests : Resistance and Counter-Resistance / Gary T. Marx -- Contesting and Resisting Security in Post-Mao China / Juha A. Vuori -- Rebelling Against Biometrics in France / Pierre Piazza -- Poking Holes and Spreading Cracks in the Wall : Resistance to National Security Policies Under Bush / Florent Blanc -- Security as Universality? : The Roma Contesting Security in Europe / Claudia Aradau -- The Political Limits of Desecuritization : Security, Arms Trade, and the EU's Economic Target / Thierry Balzacq, Sara Depauw and Sarah Leonard -- Just and Unjust Desecuritizations / Rita Floyd -- Emancipation and the Reality of Security : A Reconstructive Agenda / Joao Nunes -- Contesting Border Security : Emancipation and Asylum in the Australian Context / Matt McDonald -- Resiliencism and Security Studies : Initiating a Dialogue / Philippe Bourbeau -- Resilience as Standard : Risks, Hazards and Threats / Peter Rogers -- Pandemics as Staging Grounds for Resilient World Order : SARS, Avian Flu, and the Evolving Forms of Secure Political Solidarity / Mika Aaltola -- Conclusion / Lene Hansen.
Includes bibliographical references and index.
Keywords: Public safety -- Social aspects; Internal security -- Social aspects; National security -- Social aspects; Security, International -- Social aspects